Notes on the British Income Tax and Company Reserves - Edwards, Ronald S.; Black, Duncan (Review of Economic Studies, 1938)
Ronald S. Edwards, Duncan Black; Notes on the British Income Tax and Company Reserves1, The Review of Economic Studies, Volume 5, Issue 2, 1 February 1938,